Academic motivation at early ages: Spanish validation of the Elementary School Motivation Scale (ESMS-E) - Ramos, Marta; De Sixte, Raquel; Jáñez, Álvaro; Rosales, Javier (Frontiers in Psychology, 2022)
The Elementary School Motivation Scale (ESMS) is the only validated and adapted instrument to assess motivation in early ages and in specific domains using the Self-Determination Theory. The present study aims to validate the ESMS in Spanish population (ESMS-E). To this end, 1,190 students from the first half of Elementary education (6–10 years old) filled in the ESMS-E. To translate the instrument the back translation method was used. Internal consistency was assessed through composite reliability (CR), correlations among the dimensions and Confirmatory Factor Analysis (CFA) were used to analyze the theoretical structure proposed by the original instrument. Results showed optimal internal consistency in the different dimensions (CR = 0.701–0.901) and showed a great fit for the model (RMSEA = 0.064, CFI = 0.929, TLI = 0.913), confirming the original model with nine dimensions and the self-determination continuum. The ESMS-E is valid and reliable in the Spanish version. This validation offers a tool for researchers interested in exploring the motives that drive students in early stages in relation to specific learning domains (i.e., reading, writing and mathematics).